2018
DOI: 10.1038/s41598-018-20347-8
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of soil bacterial, archaeal and fungal communities inhabiting archaeological human-impacted layers at Monte Iato settlement (Sicily, Italy)

Abstract: Microbial communities in human-impacted soils of ancient settlements have been proposed to be used as ecofacts (bioindicators) of different ancient anthropogenic activities. In this study, bacterial, archaeal and fungal communities inhabiting soil of three archaic layers, excavated at the archaeological site on Monte Iato (Sicily, Italy) and believed to have been created in a chronological order in archaic times in the context of periodic cultic feasts, were investigated in terms of (i) abundance (phospholipid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(16 citation statements)
references
References 39 publications
2
14
0
Order By: Relevance
“…Metagenomic studies have shown that Archaea are very diverse and abundant and that they play important roles in nitrogen cycling in soils (Bates et al, ; Edwards et al, ; Siles, Öhlinger, Cajthaml, Kistler, & Margesin, ). Moreover, even though it has been suggested that they could affect plants (Taffner et al, ), which would in turn affect pest insects, there is scant information on their importance and the roles they play in these hosts (Gurung, Wertheim, & Falcao Salles, ).…”
Section: Discussionmentioning
confidence: 99%
“…Metagenomic studies have shown that Archaea are very diverse and abundant and that they play important roles in nitrogen cycling in soils (Bates et al, ; Edwards et al, ; Siles, Öhlinger, Cajthaml, Kistler, & Margesin, ). Moreover, even though it has been suggested that they could affect plants (Taffner et al, ), which would in turn affect pest insects, there is scant information on their importance and the roles they play in these hosts (Gurung, Wertheim, & Falcao Salles, ).…”
Section: Discussionmentioning
confidence: 99%
“…The reasons for the failure of the universal primers to detect Archaea are unclear; however, it seems bacterial signatures outcompete archaeal signatures, just due to slightly better primer matches, depending on the diversity within the sample. Furthermore, an archaeal primer pair (519F-806R) that has been used before for amplicon sequencing (Siles et al, 2018) detected only a small proportion of the archaeal diversity in the analyzed samples, but the same primer pair performed better when used in a nested PCR together with the primer pair 344F-1041R for the first PCR.…”
Section: Discussionmentioning
confidence: 99%
“…Archaea form another important domain of the microbes that not only inhabit extreme regions, but are also found in strong association with soils and oceans (Alves et al., ). Their rich diversity and huge abundances have been demonstrated with the help of metagenomics (Bates et al., ; Edwards et al., ; Siles et al., ), which also revealed that these organisms play important roles in the nitrogen cycling in soils – a function that was discovered not much more than a decade ago (Treusch et al., ). Archaea might directly affect their plant host (Taffner et al., ), which could indirectly affect pest insects.…”
Section: Archaeamentioning
confidence: 99%